'Algorithmic nations': seeing like a city-regional and techno-political conceptual assemblage. Issue 1 (1st January 2018) - Calzada, Igor
ABSTRACT: There are changing dynamics among political regionalization processes and the rescaling of nation-states in Europe. However, updated and timely research remains scant, ambiguous and unable to meet the challenges of data-driven societies and uneven borders. Nations' physical boundaries matter as much as political borders in their pervasive and growing algorithmic, stateless, liquid and metropolitan citizenship patterns. This paper explores these new 'connectographies' from a regional science perspective, introducing the term 'algorithmic nations' as a city-regional and techno-political conceptual assemblage. A case study is presented of the small stateless city-regionalized European nation of the Basque Country through its analytical and transitional lens, locally known as 'Euskal Hiria' (Basque city-region in the Basque language). This paper questions whether the Basque Country could evolve by (1) modifying its governmental logics and (2) merging its three separate devolved administrations (3) while enabling their direct interactions with citizens (4) through blockchain technologies as the small state of Estonia is implementing and employing cutting-edge algorithmic governance frameworks. In doing so, this paper suggests how four drivers – metropolitanization, devolution, the right to decide and blockchain – may be respectively invigorating four dynamics – geoeconomics, geopolitics, geodemocratics and geotechnologics – in this transition towards the algorithmic nations. Ultimately, this paper concludes with an algorithmic nations research and policy agenda decalogue of how these geotechnological changes might determine the future position of small stateless city-regionalized nations in the European Union.